Universality and Diversity of Human Rights in The Hadith of The Prophet PBUH: An Examination of The Book Sahih al-Bukhari and Sahih Muslim - Misbahuddin, Misbahuddin (Tasyri' : Journal of Islamic Law, 2026)
The Universal Declaration of Human Rights (UDHR), proclaimed by the United Nations in 1948, has sparked considerable controversy, particularly regarding its claim to universality. The universality of the UDHR implies that it applies to all individuals regardless of their differing backgrounds—be it in terms of religion, ethnicity, race, language, culture, economy, politics, or other aspects commonly referred to as diversity. This paper aims to explore the concept of human rights in the Prophet’s hadiths in relation to their universal and diverse dimensions. Through a qualitative analysis of selected hadiths on human rights found in Ṣaḥīḥ al-Bukhari and Shahih Muslim, this study reveals that the diversity of human rights in the Prophet’s tradition can be viewed from both conceptual and practical perspectives. Conceptually, human rights in Islam are closely tied to a trichotomic framework—the relationship between God, humans, and nature. Human rights in Islam are not grounded in individualism; rather, they tend to emphasize collective responsibility. Moreover, in a theocentric society, the enforcement of human rights in Islam is inseparable from accountability both in this world and in the hereafter. Practically, the diversity of human rights is reflected in several issues as highlighted by Abdullahi An-Na'im, such as freedom of religion or belief, the relationship between Muslims and non-Muslims, and women's rights. These practical issues are rooted in differing conceptual foundations, wherein human rights in Islam prioritize the relationship with God above all others.